Prevalence and Determinants of Cervical Abrasion among School-Going Adolescents in Puducherry, India: A Cross-Sectional Study - Sofia Sebastian; Srivenkateswaran Kothandapany; Gnanamani G; Nancy S; Mujibur Rahman K; Sathish Kumar S (National Journal of Community Medicine, 2026)
Background: Cervical abrasion, a non-carious lesion typically associated with adults, is increasingly observed in adolescents due to changing oral hygiene habits. In South India, limited community-based data exist on its prevalence and determinants. Objective: To assess the prevalence of cervical abrasion and investigate independent behavioural and clinical variables among school-going adolescents in Puducherry, India. Methods: An analytical cross-sectional study was carried among 320 adolescents from grades 8 to 12 in Puducherry, India, between January to June 2025. Standardized clinical examination was done. Data on oral hygiene practices and systemic conditions were collected using a structured questionnaire. Bivariate analysis and multivariable binary logistic regression were performed. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were reported. Results: Cervical abrasion was observed in 97 participants, yielding a prevalence of 30.3%. In multivariable analysis, aggressive toothbrushing (AOR = 5.08; 95% CI: 2.76-9.35), use of abrasive toothpaste (AOR = 6.62; 95% CI: 3.35-13.08), pica (AOR = 8.93; 95% CI: 2.82-28.24), and acid-peptic disorders (AOR = 3.61; 95% CI: 1.24-10.55) were identified as independent determinants. Sex and nail-biting did not retain statistical significance. Conclusion: Early identification and targeted preventive strategies during adolescence may reduce the long-term burden of non-carious cervical lesions.